Summer Thermal Comfort in Urban Squares: The Case of Human Tower Exhibitions in Catalonia - Òscar Saladié; Anna Boqué-Ciurana; Júlia Sevil; Jon Xavier Olano Pozo (Atmosphere)
Global warming and the increasing frequency and intensity of heat waves are resulting in more frequent unfavourable weather conditions for outdoor activities, especially during the summer. The building environment can alter weather conditions, resulting in higher temperatures (urban heat island). Human towers are cultural activities that typically take place outdoors and were declared a UNESCO Intangible Cultural Heritage in 2010. The objectives of this study are (i) to analyse the weather conditions (i.e., temperature and relative humidity) during the human tower exhibitions, (ii) to determine discomfort during the exhibitions based on the heat index (HI) resulting from the combination of temperature and humidity, and (iii) to compare records from the square with those recorded in the nearest automatic meteorological station (AMS) belonging to the Catalan Meteorological Service network. To determine the weather conditions in the squares during the human tower exhibitions, a pair of sensors recorded temperature and relative humidity data in six exhibitions performed in the summer of 2024. The temperature exceeded 30 °C in five of the six human tower exhibitions analysed. In the cases of the Santa Anna exhibition (El Vendrell) and the Sant Fèlix exhibition (Vilafranca del Penedès), one of the sensors recorded temperatures above 30 °C throughout the entire duration of the exhibition. There was a predominance of HI values falling within the caution threshold in the two sensors of three exhibitions and within the extreme caution threshold in the two sensors of the other three exhibitions. The temperature is higher in urban squares than in the surrounding rural areas. The key factor is the urban heat island phenomenon, which poses health risks to both human tower builders and attendees. Adaptation measures are therefore necessary to guarantee the safety of the participants.